HUBUNGAN ANTARA KRITERIA PEROKOK DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA KECAMATAN PRAMBANAN YOGYAKARTA - Basuki, Prastiwi Putri; Febriani, Heni (STIKES Wira Husada Yogyakarta, 2017)
ABSTRACT Acute Respiratory Infections (ARI) is a respiratory disease up or down, which can result in a spectrum of illnesses ranging from asymptomatic disease or mild infection to severe and fatal disease, depending on the causative pathogen. Smoking is a risk factor for the occurrence of ISPA, the negative impact of smoking is not only felt by the active smokers, passive smokers may also be affected. This study was to determine the relationship between the criteria of smokers with the incidence of acute respiratory infections (ARI) in children under five in the working area of Yogyakarta Prambanan District. This type of research is quantitative research with descriptive design with cross sectional analytic. Analysis using Spearman rank correlation test. Retrieving data using questionnaires and patient health status sheet obtained from Puskesmas Prambanan Yogyakarta with a sample of 96 respondents. Based on test data show that the Spearman rank p-value = 0.008 (p